Effect of Ozone Gel on Postoperative Sequelae after Surgical Removal of Impacted Lower Third Molars. - Sherwan Faisal Hamadamin; Ahmad Abdulla Haider (Erbil Dental Journal)
Background and objectives: the study aims to evaluate the efficacy of ozone gel in reducing pain, swelling, trismus and also to evaluate soft tissue healing and dry socket after surgical removal of impacted lower third molars.